The extra woman : how Marjorie Hillis led a generation of women to live alone and like it - Scutts, Joanna (Liveright Publishing Corporation, 2018)
Presents a cultural history of independent single women between the 1920s and the 1950s through the reclaimed life of glamorous guru Marjorie Hillis.